Effect of coupling in steel/aluminium laminate subjected to tensile load and bending load - Law, Ming En (Nanyang Technological University, 2023)
This project involves the study of coupling effects in steel/aluminium laminate when subjected to bending load. A practical experiment using acrylic and polycarbonate sheets to stimulate the structural response of aluminum and steel respectively was being conducted. Five different breadth sizes – 40, 60, 80, 100 and 120mm of both the acrylic and polycarbonate sheets was being pre-cut while fixing its length and thickness at 300mm and 1mm respectively. These pre- cut acrylic and polycarbonate sheets are being bonded using MTC-90 acrylic glue while keeping the total thickness of the laminate at 2mm for each specimen of the test as it gives the most prominent coupling effects. An experiment was being conducted for the various laminate breadth size under different bending load configurations. Results obtained from it was being compared to the theoretical calculations that was performed for the various breadth size using the bending deflection equation. It can be observed through the plot for the results of the experimental bending deflection test versus the theoretical calculations, it exhibits material linearity for most of the breadth sizes.